2003
DOI: 10.1002/iroh.200390025
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Standardisation Reveals a Significant Influence on the Dynamics of Bacterial Abundance in Newly Deposited River Sediments

Abstract: After a high water event of the River Danube in April 1994, bacterial cell numbers were determined in newly formed deposits in a backwater near Hainburg (Lower Austria) within a time course of 140 days. This data set shows that expressing bacterial numbers per fresh sediment volume, per sediment dry mass, or per pore-water fluid volume, respectively, yield significantly different results and ecological conlusions. These findings refer particularly to intra-study and time-course comparisons as presented in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The weighted average of the respective colony counts was used when more dilutions were countable on the plates. The counts of the indicators were converted from CFU/wet gram of faeces to CFU/cm 3 to avoid any bias due to standardisation (Farnleitner et al 2003). However, it was observed that the concentrations did not vary much when Chicago, IL) was used for data analysis and the significance level at p # 0.05 was used.…”
Section: Discussionmentioning
confidence: 99%
“…The weighted average of the respective colony counts was used when more dilutions were countable on the plates. The counts of the indicators were converted from CFU/wet gram of faeces to CFU/cm 3 to avoid any bias due to standardisation (Farnleitner et al 2003). However, it was observed that the concentrations did not vary much when Chicago, IL) was used for data analysis and the significance level at p # 0.05 was used.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were stored at 4°C and processed within three days. Prokaryotic abundance, sediment bulk density, dry mass (DM) and pore water (PW) were determined as described previously (Farnleitner et al 2003). Organic content of sediment samples was calculated by subtracting the sample weight after combusting (500°C, 4 h) from DM.…”
Section: Methodsmentioning
confidence: 99%